Development of two enzyme-linked immunosorbent assay formats for thifluzamide residues’ analysis based on distinct polyclonal antibodies - Xiaoxiao Li (Taylor & Francis Group, 2018)
Haptens 2-Methyl-4-(trifluoromethyl)thiazole-5-carboxylic acid and 2,6-Dibromo-4-(trifluoromethoxy)aniline, the two moieties of thifluzamide, were conjugated with carrier proteins for the synthesis of artificial antigens. Two distinct anti-thifluzamide polyclonal antibodies (PAb-1 and PAb-2) were produced from the immunized female Balb/c mice. The indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) in two formats based on the PAbs was developed for thifluzamide analysis. The concentration of 50% inhibition (IC50) of ELISA-1 was 1.39 mg L−1 and its limit of detection (LOD) was 0.082 mg L−1. Meanwhile, ELISA-2 had a similar IC50 of 1.96 mg L−1 and a LOD of 0.074 mg L−1 as ELISA-1. Both the raised PAbs exhibited high specificity to thifluzamide. The recoveries for spiked samples including water and wheat ranged from 72.0% to 128.4%, and the accuracy of ELISA was confirmed by high-performance liquid chromatography. In summary, the ic-ELISA might be a promising tool for simple, sensitive and rapid detection of thifluzamide residues in real samples.